“Neither Water, nor War:” the Problem of Fresh Water in International Relations of the First Quarter of the 21st Century - A. B. Likhacheva (Международная аналитика, 2024)
In this article, the author compares the objective dynamics of changes in the state of the water problem since the beginning of the 21st century, which has continued to worsen in most regions of the world, and its foreign policy dimension, noting the transition from the global water alarmism of the 1990s to the challenges for small and medium powers, in solving the problems in which no major actor is yet actively interested. Fresh water, despite the slogans at the end of the last century about future water wars, the “blue oil” and the “new gold” of the 21ST century, has not become, and is unlikely to become, the cause of confrontation between great powers, while medium and small powers are still confine themselves to more traditional forms of conflict, including in the Tigris, the Euphrates and the Jordan basins, which have been seen for decades as a testing ground for future water wars. This does not negate the role of water bodies and ecosystems in promoting development or, conversely, in perpetuating the poverty and backwardness in entire regions. Waters remain in competition as an important source of water-intensive goods that can be converted into valuable assets – water-intensive goods, energy or the ability to achieve higher levels of the Human Development Index. And, of course, they can be used to exacerbate ethnic and political conflicts. This is where the potential of Russia, the world’s second water power, comes into play, both in terms of directly regulating regional water challenges and in influencing the approaches of international organizations and associations, in which Moscow plays a prominent role.